The (In)Coherence of Canadian Education Policy Regimes with the United Nations' Refugee Education Strategy - Schutte, Valerie Rose (Université d'Ottawa / University of Ottawa, 2020)
This thesis by article contains three chapters. The first chapter provides an overview of recent developments in global refugee education policy to situate Refugee Education 2030, the United Nations High Commissioner for Refugees’ current international refugee education strategy, within global policy initiatives. It then reviews the literature on refugee education policy that informed the development of a methodology of vertical policy coherence analysis with Refugee Education 2030 to answer the research questions of the thesis. Finally, it addresses my researcher positionality and journey leading to the thesis. The second chapter contains the manuscript for an article. The purpose of the article is to analyze the vertical coherence of Canadian policy regimes towards the primary and secondary education of refugee children and youth with Refugee Education 2030. The article presents a theoretical framework for policy coherence analysis that combines policy coherence theory, policy attributes theory, and policy behaviour theory, as well as a tri-phasic methodology for vertical policy coherence analysis with an international framework designed to be adapted to different contexts to guide the development of country-specific education policies. The theoretical framework and methodology are applied to determine the categories of needs underpinning Enabling Activities of a Strategic Objective of Refugee Education 2030, to assess these needs as presented by refugee children and youth in Canada, and to analyze the coherence of Canadian education policy responses to these needs with Refugee Education 2030. The findings indicate that there are five categories of needs inherent in the Enabling Activities of the selected Strategic Objective, specifically access to education, accelerated education, language education, mental health and psychosocial support, and special education; that all of these categories of needs are present in refugee claimant and/or refugee children and youth in all of Canada’s educational jurisdictions; and that there are significant gaps in policy responses to these needs. Taken together, the findings permitted a discussion on priorities for the revision and development of refugee education policy across Canadian jurisdictions to ensure greater coherence with Refugee Education 2030. The third chapter summarizes the findings of the contextualized analysis of the vertical coherence of Canadian refugee education policy regimes with Refugee Education 2030. Additional findings that could not be incorporated in the article due to the manuscript submission guidelines Schutte iv of the intended journal of publication are then presented and discussed. The thesis concludes with reflections on my research journey.
Keywords: Refugee education; Policy coherence analysis; Primary education; Secondary education; Scoping review of policies; Canada; United Nations High Commissioner for Refugees; Refugee Education 2030